Ni-Sn transient liquid phase bonding - Siti Denielle Aziz (Nanyang Technological University, 2021)
On-engine sensors in aerospace engines are operated at high temperatures and in mechanically vibrating environment. The reliability to meet such demands and requirements has become a highly stringent and new packaging materials and approach are needed to improving microelectronics packaging to facilitate the demands. Transient liquid phase (TLP) bonding is promising as it is suitable to operate in a high-temperature environment due to its low cost and comprehensible bonding process. In this study, the approach to dealloy a Ni alloy for Ni-Sn TLP bonding technologies are studied. Fundamental investigations were carried out to investigate the results of etching Zn from Ni-Zn alloy deposition. Due to the wide difference in standard reduction potential and elemental behaviour, the deposited and etched structures were not favourable for the bonding process. The cross-sectional view of the samples had gaps, defects and voids that led to the mechanical reliability being compromised. Etched samples at 1-minute had the highest shear strength and transforming the bonds into !"!#$" intermetallic compounds (IMCs). Further, the mechanical strength and reliability of the TLP bonding joints are reduced owing to the formation of brittle IMCs.